2000
DOI: 10.1063/1.126508
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a self-organized growth in granular Co/Al2O3 multilayers

Abstract: By sequential deposition of thin layers of cobalt and alumina by sputtering, we have fabricated granular multilayers consisting of successive planes of nanosized cobalt clusters separated by alumina along the growth direction. Combining grazing-incidence small-angle x-ray scattering and transmission electron microscopy experiments, we show that, in a given range of thickness, the vertical arrangement of clusters from plane to plane is not random but shows a topology-induced self-organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 16 publications
5
65
0
Order By: Relevance
“…We give in Table I a list of the important parameters obtained from these experiments for all samples studied. Finally, the TEM pictures reveal a quasi-ordered arrangement of the Co clusters 16 that is induced by the topology of the layers: the clusters of a layer nucleate preferentially in the hollows left by the previous layer. In each layer, the average distance between the borders of adjacent clusters is of order 2 nm and approximately independent of t Co .…”
Section: Morphology and Structure Of The Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…We give in Table I a list of the important parameters obtained from these experiments for all samples studied. Finally, the TEM pictures reveal a quasi-ordered arrangement of the Co clusters 16 that is induced by the topology of the layers: the clusters of a layer nucleate preferentially in the hollows left by the previous layer. In each layer, the average distance between the borders of adjacent clusters is of order 2 nm and approximately independent of t Co .…”
Section: Morphology and Structure Of The Samplesmentioning
confidence: 99%
“…A given sample is usually made by piling up a number N (1 to 100 for the samples studied here) of these layers. 16 The deposition rates of both Co and alumina were respectively 0.114Å s −1 and 0.43Å s −1 . It was found that the amount of Co deposited on the surface is larger than the Co mass which forms clusters visible by transmission electron microscopy (TEM).…”
Section: Morphology and Structure Of The Samplesmentioning
confidence: 99%
See 3 more Smart Citations